The Development of Science Learning Achievement and Analytical Thinking of Grade 7 Students Using 5E Inquiry-Based Learning Cooperated with Graphic Organizers - Surat Kwinram,; Teerachati Noisombut,; Wittaya Worapun, (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the effectiveness of the 5E inquiry-based technique integrated with graphic organizers on grade 7 students’ science learning achievement and to investigate the effectiveness of the 5E inquiry-based technique integrated with graphic organizers on grade 7 students’ science analytical thinking. 36 Thai 7th-graders were selected as the participants of the study using purposive random sampling. The instruments were a learning management plan designed using the 5E learning technique integrated with graphic organizers, a pre-post-test for students’ learning achievement of Heat and Energy, and a pre-post-test for students’ analytical thinking. The statistics used in data analysis were mean scores, standard deviation, and a paired samples t-test. The results of the study could imply positive effects of the integration of the 5E inquiry-based technique and graphic organizers on both students’ qualities.